2012
DOI: 10.1016/j.gca.2012.03.041
|View full text |Cite
|
Sign up to set email alerts
|

The influence of source heterogeneity on the U–Th–Pa–Ra disequilibria in post-glacial tholeiites from Iceland

Abstract: We investigate the relative influence of mantle upwelling velocity and source heterogeneity on the melting rates recorded by 230 230 Th excesses and distance from the inferred plume centre is consistent with a model of decreasing mantle upwelling velocity with increasing distance from the plume axis. However, the model is not substantiated by the ( 231 Pa/ 235 U) data as the correlation with distance from the plume centre is weak. On the scale of individual eruption centres, the observed U-series are influ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 113 publications
1
14
0
Order By: Relevance
“…Concentrations of U, Th, Ra and Ba for whole rock and groundmass are within the range of data from previous U-series studies of Icelandic basalts (Condomines, et al 1981;Hemond, et al 1988a;Kokfelt, et al 2003;Kokfelt, et al 2009;Koornneef, et al 2012a;Sigmarsson 1996;Sigmarsson, et al 1992a;Sigmarsson, et al 1992b;Sigmarsson, et al 1991;Zellmer, et al 2008 (Zellmer, et al 2008). All plagioclase separates analyzed in this study had ( 226 Ra)/( 230 Th) ratios for whole rock samples in this study were both 1.05 (Table 2; Figure 6b), again similar to previous results for Icelandic basalts (Bindeman, et al 2006;Kokfelt, et al 2003;Kokfelt, et al 2009;Sigmarsson 1996;Zellmer, et al 2008 (Blundy and Wood 2003a;Fabbrizio, et al 2009).…”
Section: Uranium-series Analysessupporting
confidence: 91%
See 2 more Smart Citations
“…Concentrations of U, Th, Ra and Ba for whole rock and groundmass are within the range of data from previous U-series studies of Icelandic basalts (Condomines, et al 1981;Hemond, et al 1988a;Kokfelt, et al 2003;Kokfelt, et al 2009;Koornneef, et al 2012a;Sigmarsson 1996;Sigmarsson, et al 1992a;Sigmarsson, et al 1992b;Sigmarsson, et al 1991;Zellmer, et al 2008 (Zellmer, et al 2008). All plagioclase separates analyzed in this study had ( 226 Ra)/( 230 Th) ratios for whole rock samples in this study were both 1.05 (Table 2; Figure 6b), again similar to previous results for Icelandic basalts (Bindeman, et al 2006;Kokfelt, et al 2003;Kokfelt, et al 2009;Sigmarsson 1996;Zellmer, et al 2008 (Blundy and Wood 2003a;Fabbrizio, et al 2009).…”
Section: Uranium-series Analysessupporting
confidence: 91%
“…Note that for Population 03-2 laser data, Sm concentrations were below detection, so the value shown for Sm (the minimum value measured by laser-ablation in any of these samples) is an estimate of the maximum concentration. Data in the GeoRoc compilation for panel (a) are from the following references: (Arnorsson and Oskarsson 2007;Condomines, et al 1983;Condomines, et al 1981;David, et al 2000;Fitton, et al 2003;Grönvold and Mäkipää 1978;Hemond, et al 1993;Kempton, et al 2000;Kokfelt, et al 2003;Kokfelt, et al 2009;Koornneef, et al 2012a;Koornneef, et al 2012b;Kurz, et al 1985;Maclennan, et al 2001;Martin and Sigmarsson 2010;Nichols, et al 2002;Nicholson, et al 1991;Nicholson and Latin 1992;Sigvaldason and Oskarsson 1986;Stracke, et al 2003a;Stracke, et al 2003b;Sveinbjornsdottir, et al 1986;Tera, et al 1986;Thirlwall, et al 2004;Torssander 1988;White and Hochella 1992;Wood, et al 1979) Figure 4: Barium concentrations (in ppm) vs. anorthite concentrations (in mol % An) in plagioclase populations for Krafla samples 03KRA01 and 03KRA03. Concentrations of Ba were measured by laser-ablation ICP-MS. Anorthite content for the same spots was measured by electron microprobe for spots where Ba analyses were conducted at UCD and by laser-ablation ICP-MS where Ba analyses were conducted at OSU (see Methods for details).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to consider the impact of a pyroxenetic source lithology, we can derive a bulk partition coefficient of D sol/liq (Th) = 0.005 ± 0.002 (2 σ m ) based on melting experiments of MORB‐like pyroxenite and eclogite at 2.9–3.1 GPa [ Klemme et al ., ; Pertermann et al ., ] (see supporting information). This exercise yields a minor deviation from our baseline that trivially affects our inverse source model and corroborates other studies that have shown that the bulk partitioning behavior of Th (and U) does not vary significantly between peridotitic and pyroxenitic sources [e.g., Stracke et al ., ; Prytulak and Elliott , ; Koornneef et al ., ]. However, pyroxentic source components have been shown to melt with a much higher production rate and at greater pressures/depths than ambient mantle peridotite [ Yaxley , ; Hirschmann et al ., ; Pertermann and Hirschmann , ].…”
Section: Determining Oib Source Compositions Via Inverse Modelingmentioning
confidence: 89%
“…Iceland (Koornneef et al, 2012)), age-constrained 230 Th-226 Ra disequilibria are relatively low (closer to secular equilibrium) for the Jan Mayen region, and are notably lower at Jan Mayen Island than for the NKR. If they record the primary melt generation process, these ( 226 Ra/ 230 Th) values nearer secular equilibrium could suggest relatively high melting rates, possibly due to the presence of a more fusible lithology like eclogite.…”
Section: Model Calculations For Melt Generation Beneath the Eggvin Bankmentioning
confidence: 89%